From Fraternal Brotherhood to Murderous Cult: The Origins and Mutations of Southern Nigeria’s Confraternities from 1953 Onwards - Ben Bergman (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
The Nigerian confraternity movement in the 1950s seemed to sprout from ideas of brotherhood and chivalry, much like any U.S. fraternity might have. But twenty years later Nigerian confraternities were beheading fellow students, murdering administrators, running prostitution rings, and wreaking havoc across Southern Nigeria. What caused the transformation from the original Pyrates confraternity to the ruthless, violent organizations of the 1980s and 90s? Which factors are most responsible for the transformation? This paper will attempt to answer these questions through both historical analysis and theoretical critique of contemporary arguments concerning the corruption of confraternities. An in depth historical analysis will be conducted on the origin point of Nigeria’s first fraternities, as well as the progression and gradual corruption of values that undermined the confraternities later on. Next, this paper will give an overview of prominent academic theories concerning the subject while weighing the strengths and weaknesses of each. Finally I will offer up my own explanation for the corruption of confraternities, and tie it back in with the most successful elements of other modern theories to craft a comprehensive answer to the above questions.